Artistic Crosscurrents: Critical Vocabularies of Literature, Painting, Architecture, and Music in the Nineteenth Century - Watt, Paul (Australasian Journal of Victorian Studies, 2015)
From the late eighteenth century to well into the nineteenth century, writers—whether by accident or design—invoked vocabulary associated with one of the arts to help explain the form, function or aesthetic code of another.1 Two particularly poignantuses of such vocabulary come firstly from Goethe, with his well-known phrase “Architecture is frozen music”2 and secondly from Walter Pater’s assertion that “All art constantly aspires to the condition of music” (57). Countless such examples can be found in the works of many nineteenth-century writers. As we shall see in the articles that follow, a plethora of metaphorical and rhetorical devices (and strategies) crisscrossed writers, critical texts, and temperaments. Sometimes these connections and infiltrations are easy to discern yet at other times they are subtle and hard to detect. Such literature often aimed to educate the reader, and inspired a number of “different sorts of consequential writings—aesthetic, economic, pedagogical, political—and organized them around narratives of ethical development” (Miller 1).